Physical properties of CdSxTe1-x thin films prepared by close spaced sublimation method - Gaewdang, Thitinai; Wongcharoen, Ngamnit (My University, 2017)
CdSxTe1-x(0 ≤ x ≤ 1) thin films were prepared on clear quartz glass substrate by close spaced sublimation method using stoichiometric mixed powders of pure CdS and CdTe compounds. Crystal structure of CdSxTe1-xthin films was cubic structure with a preferential orientation of (111) plane when the S mole ratio less than 0.2. However, For the composition 0.2 ≤ x ≤ 0.8, the cubic and the hexagonal phases were found to coexist in the system and the films became less preferentially oriented whereas CdS thin films formed in the hexagonal phase with a preferential orientation of (002) plane. SEM micrographs showed the grain size decreased when the S content increased. As the S content increased, the energy gap value of CdSxTe1-xthin films varied from 1.48 eV (for CdTe) to 2.25 eV (for CdS). Dark electrical sheet resistance of CdSxTe1-xthin films decreased as a function of S content to minimum value about 2.24×107Ω/sq for x=0.8 and then slightly increased to 4.13×107Ω/sq for x=1.0. From the transient photoconductivity measurements, the highest photosensitivity value about 60.0 was obtained for the films with x = 0.8.
Keywords: CdSxTe1-x thin films; Close spaced sublimation; Photosensitivity; XRD